Investigation of students’ conceptual understanding of fluids in Kupang City and Sabu Raijua District - Muki, Beata Graceshela; Aviyanti, Lina; Nawas, Abu (Momentum: Physics Education Journal, 2025)
This study analyzes students’ concept understanding ability on fluid material in Kupang City and Sabu Raijua Regency. Using the descriptive quantitative method, this study involved 332 high school students in grades XI and XII of science specialization in the age range of 14-18 years, with research samples in Kupang City including 91 male students and 160 female students, while samples in Sabu Raijua Regency included 33 male students and 48 female students. The instrument, in the form of 12 multiple-choice questions based on cognitive indicators of understanding (C2), was declared reliable, with Cronbach’s Alpha 0.82 in the outstanding category. The results showed that students in Kupang City had a concept understanding level of 39.54% (less understanding category), lower than students in Sabu Raijua Regency with a percentage of 45.47% (sufficient understanding category). Gender analysis revealed that female students were superior to male students in all indicators, especially in the comparing indicator. However, weaknesses were seen in the summarising and explaining indicators in both regions. Rasch modeling analysis with the help of WINSTEPS showed variations in students’ abilities between the low to sufficient categories. The findings are expected to be a reference for teachers to design contextual, problem-based, and collaborative learning and utilize learning media to improve students’ concept understanding in Physics.